Teacher job performance: The mediating role of work culture - Nurbaya, Sitti; Ramly, Mansyur; Sinring, Bahar; Latif, Baharuddin (Advances in Social Sciences Research Journal, 2019)
The purpose of this study is to explain the effect of competence, motivation and work discipline on culture; to know and explain the effect of competence, motivation and work discipline on honorary teacher performance; to know and explain the effect of work culture on honorary teacher; and knowing to explaining the effect of competence, motivation and work discipline as a mediates work culture on honorary teacher performance on elementary school teachers in Makassar City. The study was conducted in elementary schools with a population of elementary school honorary teachers who had a Limited duration contract in 8 sub-districts in Makassar City totaling 1,495 people. A sample of 317 respondents used the Slovin formula. The data from the questionnaire were analyzed using the Structural Equation Model using AMOS 18. The results of the study found that the work competence, motivation and discipline directly had a positive and significant effect on teachers work culture. Work competence, motivation discipline directly has a positive and significant effect on honorary teacher performance. Teachers work culture directly has a positive and significant effect on honorary teacher performance. The three exogenous variables (competence, work discipline and work motivation) have a significant positive effect on honorary teacher performance as a mediating role of teacher's work culture.